The Effect of the Joyful Learning Method on Students' Learning Outcomes in Mathematics in Class III - Selani Julia Habeahan; Patri Janson Silaban; Nova Florentina Ambarawati; Rumiris Lumbangaol; Darinda Sofia Tanjung (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
Students who have difficulty learning in mathematics lessons get unsatisfactory learning results and incomplete grades with KKM. Students who have difficulty learning in mathematics lessons get unsatisfactory learning results and incomplete grades with KKM. Quantitative research method is a research method based on positive philosophy used to research on research instruments, quantitative / statistical data analysis, with the aim of testing hypotheses that have been set. This research used is an experimental method researcher. The results of students' mathematics learning before being given treatment obtained an average value of 50.80 The results of the normality test were 0.128, so it can be concluded that the results of the pretest learning are normally distributed. The results of learning mathematics students after being given treatment obtained an average score of 72.69. The normality test result is 0.117, so it can be concluded that the posttest learning results are normally distributed. It can be proven that with a correlation coefficient value of 0.846 which is in very strong interspension. The results of the T-test calculation to find out whether the hypothesis is accepted or rejected, the ttable ≥ is 9,118 ≥ 1,692 which means that there is an influence of Joyful Learning on student learning outcomes. Thus Ha was accepted and Ho was rejected